Applicability of the Delplot method for the determination of catalytic reaction sequences: Hydrodeoxygenation of γ-valerolactone on Ni2P/MCM-41. (21st September 2020) - Yun, Gwang-Nam; Tyrone Ghampson, I.; Movick, William J.; Vargheese, Vibin; Kobayashi, Yasukazu; Ted Oyama, S.
Graphical abstract: Highlights: Hydrodeoxygenation of γ-valerolactone on Ni2 P/MCM-41 produces butane and pentane. Contact time results suggests a reaction sequence that first forms pentanoic acid. Delplot analysis does not agree with the analysis based on the contact time results. An overly large rate constant in a later step is responsible for the disagreement. Since rate constants are not known a priori the Delplot method cannot provide sequences. Abstract: Contact-time measurements based on sites are used to investigate the reaction sequence of the hydrodeoxygenation of γ-valerolactone (GVL) on Ni2 P/MCM-41. The study is carried out at 300 °C and 0.5 MPa with site times of 0.29–6.1 s. A reaction network is proposed in which pentanoic acid and 2-methyltetrahydrofuran (2-MTHF) are formed in parallel initially and pentanal, butane and pentane are formed subsequently. A first-rank Delplot analysis (selectivity) gives a good fit, but higher-rank Delplots do not. The lack of applicability is explained by the magnitude of the rate constants, in which the rate constant for one of the later steps (the consumption of pentanal) is substantially larger than those for the preceding steps. For this reason, pentanal demonstrated the characteristics of a primary product and consequently affected the discrimination of higher rank products. A simulation of a model sequence with assumed rate constants confirms the reason why the Delplot method does not work for this reaction. Since the rate constants cannot be determined a priori to be of close magnitude, the Delplot method cannot be generally used to ascertain reaction sequences.